Mitochondrial genomes reveal an east to west cline of steppe ancestry in Corded Ware populations - Juras, Anna; Chyleński, Maciej; Ehler, Edvard; Malmström, Helena; Żurkiewicz, Danuta; Włodarczak, Piotr; Wilk, Stanisław; Peška, Jaroslav; Fojtík, Pavel; Králík, Miroslav; Libera, Jerzy; Bagińska, Jolanta; et al. (Scientific reports, 2018)
From around 4,000 to 2,000 BC the forest-steppe north-western Pontic region was occupied by people who shared a nomadic lifestyle, pastoral economy and barrow burial rituals. It has been shown that these groups, especially those associated with the Yamnaya culture, played an important role in shaping the gene pool of Bronze Age Europeans, which extends into present-day patterns of genetic variation in Europe. Although the genetic impact of these migrations from the forest-steppe Pontic region into central Europe have previously been addressed in several studies, the contribution of mitochondrial lineages to the people associated with the Corded Ware culture in the eastern part of the North European Plain remains contentious. In this study, we present mitochondrial genomes from 23 Late Eneolithic and Bronze Age individuals, including representatives of the north-western Pontic region and the Corded Ware culture from the eastern part of the North European Plain. We identified, for the first time in ancient populations, the rare mitochondrial haplogroup X4 in two Bronze Age Catacomb culture-associated individuals. Genetic similarity analyses show close maternal genetic affinities between populations associated with both eastern and Baltic Corded Ware culture, and the Yamnaya horizon, in contrast to larger genetic differentiation between populations associated with western Corded Ware culture and the Yamnaya horizon. This indicates that females with steppe ancestry contributed to the formation of populations associated with the eastern Corded Ware culture while more local people, likely of Neolithic farmer ancestry, contributed to the formation of populations associated with western Corded Ware culture.
Keywords: Rusko; starobylá DNA; Grassland; Genome, Mitochondrial; Female; Russia; pastviny; ženské pohlaví; Humans; mužské pohlaví; běloši; lidé; Male; genom mitochondriální; DNA, Ancient; White People; dějiny starověku; History, Ancient